Keterikatan Akademik pada Mahasiswa: Bagaimana Peranan Dukungan Sosial dan Efikasi Diri Akademik? - Rakib, Mohammad Indra; Matulessy, Andik; Suhadianto, Suhadianto (JIWA: Jurnal Psikologi Indonesia, 2025)
There are four significant roles of academic engagement in the learning process: creating productive learning, predicting how well students perform in their studies, providing educational institutions with considerations for necessary interventions, and offering feedback to educators regarding the effectiveness of their teaching. This study aims to analyze the relationship between social support and academic self-efficacy with academic engagement. The research employs a quantitative correlational method with a total of 285 student respondents selected through random sampling. The study utilizes parametric multiple linear regression analysis techniques. The findings indicate a significant positive correlation between social support and academic self-efficacy with academic engagement, both individually and collectively. Additionally, it was found that social support and academic self-efficacy account for 52.2% of the variance in academic engagement. Through social support and academic self-efficacy, students can enhance their academic engagement, enabling them to face academic challenges optimally.